1130 An Obstructed Morgagni Hernia in Adulthood, Could Regular Cocaine Use Have Exacerbated Symptoms?. (12th October 2021) - Izard, C; Thorne, E; Ghallab, M; Agrawal, A
Abstract: Introduction: Morgagni hernias are an uncommon form of diaphragmatic hernia, it is rare for them to be diagnosed in adulthood and they are often asymptomatic in this population. Case Report: We report a case of a 26-year-old female who used cocaine on a weekly basis who presented to the emergency department with an acutely obstructed right-sided Morgagni's hernia. She underwent laparotomy which demonstrated transverse colon with ischaemic associated omentum inside the hernia. The hernia was reduced, the ischaemic omentum was excised and the 4x4cm diaphragmatic defect closed with 2-0 ethibond without mesh. Conclusions: Following review of the literature, the medical risks of cocaine use are well documented, however they focus on the risks from a pharmacological perspective. Further thought should be given to the effects of inhalant cocaine use and how this may exacerbate herniation from the drastic changes in intrathoracic pressure during inhalation of the substance, this is a new possible risk of cocaine use that is not previously mentioned in the literature and warrants further investigation.